1993
DOI: 10.1111/j.1365-2222.1993.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to four common inhalant allergens within 302 nuclear families

Abstract: The coincidence of allergic sensitization was investigated in 302 school-aged children and their parents. Specific sensitization to four common inhalant allergens (grass and birch pollens, cat dander, Dermatophagoides pteronyssinus) was ascertained by means of skin-prick tests (SPT) carried out on the complete family unit at the beginning of a 22-month follow-up period. The same test procedure was then repeated on the children twice at 11-month intervals to provide cumulative prevalences of sensitization. A cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 18 publications
1
51
0
Order By: Relevance
“…Skin prick testing was not performed in the parents [4, 5, 6, 7], but evaluation of the health questionnaires revealed no difference in the reported prevalence of allergy between immigrant and Dutch parents (table 2), though the prevalence of allergy in Surinam parents was relatively high (40%). Table 2 further shows that multiple positive skin prick reactions (two or more) were more prevalent in Moroccan and Surinam children (14.2 and 35.0%, respectively), as compared with Dutch and Turkish children (8.7 and 7.4%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin prick testing was not performed in the parents [4, 5, 6, 7], but evaluation of the health questionnaires revealed no difference in the reported prevalence of allergy between immigrant and Dutch parents (table 2), though the prevalence of allergy in Surinam parents was relatively high (40%). Table 2 further shows that multiple positive skin prick reactions (two or more) were more prevalent in Moroccan and Surinam children (14.2 and 35.0%, respectively), as compared with Dutch and Turkish children (8.7 and 7.4%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Family history of allergy is the most prominent risk factor for allergic disease [4, 5, 6, 7], but other socio-demographic factors, like economic status, number of siblings and birth order [8], show strong associations as well.…”
Section: Introductionmentioning
confidence: 99%
“…This panel of four allergens was expected to identify the majority of individuals with atopic sensitization to common allergens [24]. The observed associations with the use of QACs suggest that occupational exposure may induce sensitization to non-work-related allergens.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have evaluated parent-of-origin effects on the development of asthma and allergic susceptibility in offspring. There is strong evidence that a maternal history of allergic disease has more influence than paternal history over subsequent allergic phenotypes in offspring (18)(19)(20), and several birth cohort studies have demonstrated that maternal but not paternal history of asthma was an important predictor of subsequent wheeze in early childhood (21)(22)(23). Maternal history of asthma also appears to modify the effects of environmental factors that promote the development of asthma (24,25).…”
Section: Discussionmentioning
confidence: 99%